PENGEMBANGAN SISTEM PENYEDIAAN AIR MINUM DALAM MENINGKATKAN PELAYANAN PUBLIK: (Studi pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Halmahera Barat) - S Baranyanan, Nditi (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2024)
Development of Drinking Water Supply Systems to Improve Public Services (Study at the Public Works and Spatial Planning Department of West Halmahera Regency). This study will explain the development of a Drinking Water Supply System (DWSS) at the Public Works and Spatial Planning Office of West Halmahera Regency. It will also examine the elements that facilitate and impede the development of DWSS. The aim of this research is to analyze the supporting and inhibiting factors for the development of a DWSS. The author uses a qualitative descriptive research method. Improving the DWSS consists of Physical Aspects (Technical Aspects) and non-Physical Aspects (Institutional, Management, Financial, Community Role and Law) as stated in Government Regulation Number 16 of 2005, concerning Development of the DWSS. The research results show that in the physical (technical) aspect, the DWSS have been included in the priority program of the West Halmahera Regency Government. In the Non-Physical Aspect, it is known that the supporting factors in improving DWSS in West Hamahera Regency, namely from the Technical Aspect, Institutional, Community Role and Finance. Meanwhile, the inhibiting factors in the development of the DWSS in West Halmahera Regency are the management aspects and law. Thereefor, commitment is needed from the West Halmahera Regency Government to improve public services through human resource management and implementation of regulatiosns.